The Effect of Boycott Attitude, Subjective Norms, and Perceived Behavioral Control on Participation with Intention as Mediator Variable - Ridwan, Habib; Prananta, Widya (LifeSciFi, 2026)
This study is motivated by the increasing consumer boycott movement against brands associated with the Israel Palestinian conflict, particularly unilever products, and the gap between publicly expressed boycott intentions and actual consumer behavior. The study aims to analyze the effects of boycott attitude, subjective norms, and perceived behavioral control on boycott participation, with boycott intention as a mediating variable within the theory of planned behavior framework. A quantitative approach was employed using a survey-based questionnaire administered to 120 respondents in Semarang City who had boycotted Unilever products within the past month. Respondents were selected through purposive sampling, and data were analyzed using PLS-SEM. The results indicate that boycott attitude, subjective norms, and perceived behavioral control do not have a significant direct effect on boycott participation. However, these variables have a positive and significant effect on boycott intention, which subsequently has a significant effect on boycott participation and mediates the relationship between psychological factors and actual boycott behavior. This study concludes that boycott intention plays a crucial mediating role in explaining consumer boycott participation and confirms the relevance of the Theory of Planned Behavior in understanding moral and political boycott behavior toward fast moving consumer goods brands in developing countries.